Expanding Trade within Africa : The Impact of Trade Facilitation - Njinkeu, Dominique; Wilson, John S.; Fosso, Bruno Powo (Washington, DC: World Bank, 2012)
This paper examines the impact of trade facilitation on intra-African trade. The authors examine the role of trade facilitation reforms, such as increased port efficiency, improved customs, and regulatory environments, and upgrading services infrastructure on trade between African countries. They also consider how regional trade agreements relate to intra-African trade flows. Using trade data from 2003 to 2004, they find that improvement in ports and services infrastructure promise relatively more expansion in intra-African trade than other measures. They also show that, almost all regional trade agreements have a positive effect on trade flows.